2005
DOI: 10.1111/j.1474-9726.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular domain of p75NTR as a determinant of cellular reducing potential and response to oxidant stress

Abstract: SummaryThe low-affinity neurotrophin receptor, p75NTR, has been found to be pro-or anti-apoptotic depending upon the cell in which it is expressed. Reactive oxygen species play a major role in apoptosis induction and enactment. Using two polyclonal PC12 populations that, respectively, do or do not express p75NTR, this paper demonstrates that p75NTR expression confers resistance to oxidant stress upon PC12 cells maintained in serum-containing medium. The effect of p75NTR on cell survival is mimicked in p75-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 64 publications
2
46
1
Order By: Relevance
“…Therefore, our results support a model in which oxidative stress promotes ligand-independent cleavage of p75 NTR by TACE and ␥-secretase, leading to axonal degeneration and programmed cell death. Although our findings demonstrate that oxidants can trigger activation of p75 NTR -mediated apoptotic signaling in neurons, a previous report using PC12 cells found the intracellular domain of the receptor to have antioxidant capability, thereby conferring resistance to ROS (85). Because p75 NTR has been shown to have cell-specific effects on survival, cleavage of the receptor in response to oxidative stress may confer death in specific populations of postmitotic neurons, but similar signaling mechanisms may lead to cell survival in other non-mitotic cell types.…”
Section: Although Most Investigations Of P75contrasting
confidence: 89%
“…Therefore, our results support a model in which oxidative stress promotes ligand-independent cleavage of p75 NTR by TACE and ␥-secretase, leading to axonal degeneration and programmed cell death. Although our findings demonstrate that oxidants can trigger activation of p75 NTR -mediated apoptotic signaling in neurons, a previous report using PC12 cells found the intracellular domain of the receptor to have antioxidant capability, thereby conferring resistance to ROS (85). Because p75 NTR has been shown to have cell-specific effects on survival, cleavage of the receptor in response to oxidative stress may confer death in specific populations of postmitotic neurons, but similar signaling mechanisms may lead to cell survival in other non-mitotic cell types.…”
Section: Although Most Investigations Of P75contrasting
confidence: 89%
“…5,6 We have reported that p75NTR is a cytoplasmic antioxidant and mitochondrial oxidant in neural crest cell lines. 9, 10, 11 We have defined its antioxidant signaling pathway to involve neurotrophin binding to p75NTR; upregulation of the cholesterol biosynthetic pathway; palmitoylation of p75NTR; phosphorylation of p75NTR; cleavage of p75NTR by α- and γ-secretase to its intracellular fragment, p75ICD; translocation of p75ICD to the nucleus; and phosphorylation of Akt. 10,11 Its mitochondrial oxidant pathway involves phosphorylation of JNK and ‘leakiness' of Complex II to superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…4,33 Its independent receptor function is thought to involve binding of NGF, BDNF or NT-3, 7 cleavage of the holoreceptor to its intracellular fragment, 34 and translocation of the intracellular fragment to the nucleus, 35 where it acts as a transcription factor to upregulate expression of, among other things, cell matrix proteins 13 and enzymes responsible for the de novo synthesis of cholesterol. 8 The ‘naked' p75NTR includes a ‘death domain' and has been shown to have apoptosis-inducing properties, 36 whereas the NGF-bound p75NTR is variably pro- or anti-apoptotic 12,37 and pro- or anti-oxidant, 9,11 depending on the cellular milieu in which it is expressed. The latter paradox most likely relates to the finding that signaling through p75NTR proceeds through a branch point that can lead to activation of apotosis-inducing JNK activation or apoptosis-suppressing NF-κB and IAP activation, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in our laboratory and those of others demonstrate that Bcl-2 exerts its effects at least in part by a mechanism that includes a shift in the cellular capacity for glutathione turnover. [9,[11][12][13][35][36][37][38][39] Not surprisingly, other studies link both the initiating and subsequent steps involved in the apoptotic process to exposure of the cell to reactive oxygen species [39,40] and demonstrate release of cytochrome c from the mitochondrion with a resultant breakdown in electron transport and increased formation of endogenous reactive oxygen species. [ 39,41,42] The caspases, enzymes critical for the enactment of apoptosis, are accordingly cysteinerich and redox-active.…”
Section: Discussionmentioning
confidence: 99%